Effectivity of prebiotic mannan oligosaccharides as the immunity enhancer and growth response on whiteleg shrimp Litopenaeus vannamei against white spot disease - Prastiti, Linuwih Aluh; Yuhana, Munti; Widanarni, Widanarni, (Indonesian Society of Scientific Aquaculture (ISSA), 2018)
ABSTRACT This study aimed to evaluate the immune response and growth performance of white shrimp administered with prebiotic mannan oligosaccharides (MOS) with dosages of (0%, 0.2%, 0.4%, and 0.8% in diet) and used in the feeding trial. Shrimps (Litopenaeus vannamei) (the initial average weight was 3.416±0.064 g) were fed at satiation, three times a day. A completely randomized design was used in the study. Shrimps were cultured at the stock density of 15 shrimps 40/L for each treatment in triplicates. After 30 days of the feeding trial, shrimp were challenged with white spot syndrome virus filtrate by intramuscular injection. The total gut bacteria, total haemocyte count (THC), phenoloxydase (PO), and respiratory burst (RB) activity were observed 4 times, before the experiment, day 30th before challenge test, day 32nd after challenge test, and day 36th the end of the experiment. The shrimp survival was observed at day 36th to evaluate the immune responses. The results showed that THC, PO activity, RB activity, growth performance, and shrimp survival administered with prebiotic 0.8% were significantly higher (P<0.05) than control. The administration of prebiotic with dose 0.8% was the best result and could effectively improve the immune responses and growth performance of whiteleg shrimp. Keywords: prebiotic, whiteleg shrimp, white spot disease ABSTRAK Tujuan dari penelitian ini adalah untuk mengevaluasi respons imun dan performa pertumbuhan pada udang vaname yang diberi prebiotik mannan-oligosaccharides (MOS) dengan dosis berbeda (0%, 0,2%, 0,4%, dan 0,8%) pada pakan. Udang vaname (Litopenaeus vannamei) (dengan rata-rata bobot 3,41 ± 0,06 g) diberi pakan tiga kali sehari secara at satiation. Penelitian ini menggunakan rancangan acak lengkap. Udang dipelihara dengan kepadatan 15 ekor per 40/L pada setiap perlakuan dengan tiga kali pengulangan. Setelah 30 hari pemberian pakan, udang diuji tantang menggunakan white spot syndrome virus dengan diinjeksi secara intramuskular. Total bakteri usus, total haemocyte count (THC), aktivitas phenoloxydase (PO), dan aktivitas respiratory burst (RB) diamati 4 kali, yaitu sebelum perlakuan hari ke-30 sebelum uji tantang, hari ke-32 setelah uji tantang, dan hari ke-36 pada akhir penelitian. Hasil penelitian menunjukkan bahwa THC, aktivitas RB, aktivitas PO, performa pertumbuhan, dan kelangsungan hidup yang diberi prebiotik dengan dosis 0,8% lebih tinggi (P<0,05) jika dibandingkan dengan kontrol (dosis 0%). Pemberian prebiotik dengan dosis 0,8% merupakan hasil terbaik dan secara efektif mampu meningkatkan respons imun dan performa pertumbuhan pada udang vaname. Kata kunci: prebiotik, udang vaname, white spot disease